The rabbit and the pick-up truck. (Economist, 1996)
Looks at how Microsoft is taking over the Internet from Netscape. History of Netscape; The creation of the Internet computer language Java by Microsoft for its Internet Explorer; How Internet Explorer matches Netscape's Navigator almost identically; Marketing of Explorer; How Netscape has a grip on the market with its endless introduction of innovations; Advantages of Netscape's product.